2018
DOI: 10.1111/1365-2656.12835
|View full text |Cite
|
Sign up to set email alerts
|

Responses of insect herbivores and their food plants to wind exposure and the importance of predation risk

Abstract: Abstract1. Wind is an important abiotic factor that influences an array of biological processes, but it is rarely considered in studies on plant-herbivore interactions.2. Here, we tested whether wind exposure could directly or indirectly affect the performance of two insect herbivores, Plutella xylostella and Pieris brassicae, feeding on Brassica nigra plants.3. In a greenhouse study using a factorial design, B. nigra plants were exposed to different wind regimes generated by fans before and after caterpillars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…In a previous study (Chen et al. ), P. brassicae exposed to wind developed slower but attained more biomass. Predation of caterpillars by birds (Great Tits) was considerably reduced when reared on plants exposed to wind.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…In a previous study (Chen et al. ), P. brassicae exposed to wind developed slower but attained more biomass. Predation of caterpillars by birds (Great Tits) was considerably reduced when reared on plants exposed to wind.…”
Section: Discussionmentioning
confidence: 72%
“…In a previous study, we reported that caterpillars of P. xylostella are also more strongly disturbed by wind than the caterpillars of P. brassicae (Chen et al 2018). The higher mortality of P. xylostella in response to rainfall, especially when occurring at higher frequencies (80% reduction), is even stronger than mortality caused by wind exposure (10%; this study, Chen et al 2018). Eggs and (early) first-instar larvae of Lepidoptera are the most vulnerable life stages and mortality during each of these stages can be significant (>40%; Zalucki et al 2002).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations